A facile lead acetate conversion process for synthesis of high‐purity alpha‐lead oxide derived from spent lead‐acid batteries. Issue 1 (19th July 2018) - Yu, Wenhao; Yang, Jiakuan; Li, Mingyang; Hu, Yuchen; Liang, Sha; Wang, Junxiong; Zhang, Peiyuan; Xiao, Keke; Hou, Huijie; Hu, Jingping; Kumar, Ramachandran Vasant
Abstract: BACKGROUND: The lead oxide product recovered from spent lead‐acid battery paste via the hydrometallurgical route usually contains many impurity elements, i.e. Ba and Fe. In this paper, a facile lead acetate conversion process was proposed for synthesis of high‐purity alpha‐lead oxide (α‐PbO) derived from spent lead‐acid batteries. RESULTS: The desulfurized lead paste was leached with acetic acid and hydrogen peroxide to prepare lead acetate solution, which was then reacted with sodium hydroxide solution to synthesize high‐purity α‐PbO. The doses of acetic acid and hydrogen peroxide were the two key parameters for the removals of the impurities, due to their dominant effects on the pH and redox potential of the leaching step. Under the optimized conditions (the molar ratios of CH3 COOH/Pb of 2.00, H2 O2 /PbO2 of 3.5, and NaOH/Pb of 2.5), the high‐purity α‐PbO product with impurities of 20.5 mg kg −1 Fe and 1.5 mg kg −1 Ba was prepared, which were the lowest impurities content in lead product recovered via a hydrometallurgical route compared with previous literature. The total removal efficiencies of impurities Ba and Fe reached 99.9 wt% and 99.0 wt%, respectively. The total recovery efficiency of Pb from the spent lead paste was 92.6 wt%. CONCLUSION: The proposed acetic acid leaching process was proved to be an effective strategy to remove the impurities via a hydrometallurgical route. The recovered high‐purity α‐PbO could be used as the positive active materials for lead‐acid battery. This study could provide insights into the impurities removal in the hydrometallurgical recovery of spent lead paste. © 2018 Society of Chemical Industry